Outcomes of chlorhexidine lavage without capsulectomy versus complete capsulectomy after lead extraction for the treatment of cardiac implantable electronic device infection. (28th February 2023) - Diaz, Juan Carlos; Marin, Jorge E.; Aristizabal, Julian M.; Bastidas, Oriana; Hoyos, Carolina; Matos, Carlos; Lopez‐Cabanillas, Nestor; Matias, Jose; Di Biase, Luigi; Romero, Jorge; ,
Abstract: Introduction: Capsulectomy is recommended in patients with cardiac implantable electronic device (CIED) infection after transvenous lead extraction (TLE) but is time‐consuming and requires extensive tissue debridement. In this study, we describe the outcomes of chlorhexidine gluconate (CHG) lavage in lieu of capsulectomy for the treatment of CIED infections. Methods: This retrospective study included patients who underwent TLE for CIED‐related infections in two institutions in Colombia. In the capsulectomy group, complete capsulectomy was performed after hardware removal. In the CHG group, exhaustive lavage of the generator pocket with 20 cc of CHG at 2% followed by irrigation with approximately 500 cc of normal saline (0.9% sodium chloride) was performed. The primary outcomes included reinfection and hematoma formation in the generator pocket. Secondary outcomes included the occurrence of any adverse reaction to chlorhexidine, the need for reintervention, infection‐related mortality, and total procedural time. Results: A total of 102 patients (mean age 67.2 ± 13 years, 32.4% female) underwent CIED extraction with either total capsulectomy ( n  = 54) or CHG ( n  = 48) lavage. Hematoma formation was significantly higher in the capsulectomy group versus the CHG group (13% vs. 0%, p  = .014), with no significant differences in the reinfection rate. Capsulectomy was associated with longer procedural time (133.7 ± 78.5 vs. 89.9 ± 51.8 min, p  = .002). No adverse reactions to CHG were found. Four patients (4.3%) died from worsening sepsis: three in the capsulectomy group and one in the CHG group ( p  = .346). Conclusions: In patients with CIED infections, the use of CHG without capsulectomy resulted in a lower risk of hematoma formation and shorter procedural times without an increased risk of reinfection or adverse events associated with CHG use. Abstract : In 102 patients with cardiac implantable electronic device (CIED) infection, chlorhexidine gluconate (CHG) lavage was associated with a lower risk of hematoma and shorter procedural time compared to capsulectomy, with no significant differences in the rate of reinfection. There were no adverse events associated with the use of CHG.